Extractivism and the ecology of research infrastructure: digitizing precarious materialities in Iquitos, Peru - Amanda M. Smith (Tapuya)
How might the creation of digital research infrastructure for preserving archival materials in Latin America resemble the infrastructure of extractivism? This essay examines the development of a digital repository for one of the most important collections of Amazonian history, culture, and politics at the Biblioteca Amazónica in Iquitos, Peru. Funded in part by the Modern Endangered Archives Program (MEAP) at the University of California, Los Angeles, the project seeks to digitally catalog and preserve photographs, newspapers, maps, and local journals at risk of further damage by humidity, rodents, lack of funding, and potential fires. In dialogue with critical infrastructure studies, I consider how this otherwise altruistic project fits into the broader landscape of extractive infrastructure in the Amazon region. To problematize what materialities might be flattened in the process of digitalization and their implications for the potential digital colonialism of the project, I compare the MEAP research infrastructure to other infrastructural projects in the Iquitos area, with special emphasis on the kinds of relational encounters that Iquiteños improvise when infrastructure does not work as intended. I argue that creating similar opportunities to engage and struggle with digital research technologies has the potential to transform them for local use and complicate their potentially extractive qualities.